Naturalistic decision-making in natural disasters: an overview - Bouafia, Mohammad; Zahari, Rustam Khairi (OMICS International, 2017)
Decision-making can take place in many settings: daily life problems, financial issues, health care matters or in emergencies and situations that require quick and high-risk decisions to be made. In natural or man-made disasters, the immediate decisions are crucial for effective mitigation and management. Thus, the Decision-makers during such situations must process a large amount of unreliable and incomplete information under sharp time restrictions and critical judgments are frequently made under pressure and high stake. The purpose of this paper is to present the decisionmaking process in real-life settings focusing on the recognition-primed model (RPD) in an attempt to understand how decisions are made in emergencies and natural disasters. Literature review was conducted and it was found that the dynamic behaviour of disasters requests the decision-makers to allocate resources and attention to collaboration and coordination. Decision-making, therefore, is a sensitive task of all management actors especially emergencies and disasters managers and the effective response to such calamities depends on how effective and timely are the decisions that have been made.